PENGADAAN OBAT DI GUDANG FARMASI RUMAH SAKIT RAJAWALI CITRA BANTUL - Dendo, Angelina; Subandi, Subandi (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2026)
This study aims to obtain information on drug procurement in pharmacy warehouses, including the purchase method of "hiba" or "dropping" and products at Rajawali Citra Hospital, Bantul Regency, Yogyakarta. The type of research is descriptive qualitative. The informants in this study were the head of the pharmacy installation warehouse and the acting logistics administrator of the pharmacy warehouse. The results of this study indicate that drug procurement is carried out using the national formulary and hospital formulary, in the form of an integrated information system. Its implementation has met the Ministry of Health of the Republic of Indonesia's Health Standard Number 72 of 2016, including procurement. The challenges encountered are the availability of Medanamamic acid tablets in large pharmaceutical companies and long delivery wait times. Therefore, it is necessary to implement a more efficient supply chain management system and establish stronger partnerships with distributors to ensure drug availability and reduce the duration of treatment